Pengaruh Oral Hygiene Terhadap Kejadian Penyakit Gingivitis pada Siswa SMP Pondok Pesantren Darul Aman Lengkese Kabupaten Takalar - Aisyah Ahmad Rani; Andi Yusuf; Muhammad Syafar; Muhammad Saleh; Sainuddin Sainuddin; Siti Alfah (GLOBAL HEALTH SCIENCE, 2020)
Gingivitis is the most common periodontal disease in society, especially in adolescents. Dental and oral hygiene are closely related to plaque on the surface of the teeth, plaque influences the inflammatory process of soft tissue around the teeth, one of which is gingivitis. This study aimed to determine the effect of oral hygiene on gingivitis disease in students of Darul Aman Lengkese Islamic Boarding School, Takalar Regency. This study used descriptive analytic method with a cross-sectional approach. The data analysis used was descriptive analysis with percentage, bivariate with chi-square test, and multivariate with logistic regression test. There was correlation between oral hygiene and the occurrence of gingivitis disease (p-value = 0.001), there was no correlation between sex and occurrence of gingivitis disease (p-value = 0.605), there was correlation between age and occurrence of gingivitis disease (p-value = 0.004), there was correlation between the habit of brushing teeth and the occurrence of gingivitis disease (p-value = 0.003), there was correlation between the awareness and the occurrence of gingivitis disease (p-value = 0.000). Based on the multivariate analysis, habit and knowledge were the most influential values among on the incidence of gingivitis in junior high school students of Darul Aman Lengkese Islamic Boarding School in Takalar Regency. Keywords: gingivitis disease; oral hygiene; tooth brushing habits